Techno-economic and sustainability analysis of siloxane removal from landfill gas used for electricity generation. (15th July 2022) - Amaraibi, Rarosue J.; Joseph, Babu; Kuhn, John N.
Abstract: A technoeconomic analysis (TEA) and life cycle assessment (LCA) was conducted on the use of landfill gas (LFG) for electricity generation using an internal combustion engine. This study provides insights that can guide LFG waste to energy (WTE) operators on decisions concerning installation of contaminant removal from LFG for electricity generation. Four scenarios were analyzed; the first (Scenario 1) was a facility with a single siloxane removal unit (SREU) sized for 6 months of continuous use, the second (Scenario 2) was a facility with parallel SREUs sized for one month of use, the third (Scenario 3) was a facility with no SREU, and the fourth was a facility that flared all LFG captured. The TEA revealed that the chiller cost was over 50% the total purchase cost of the LFG pre-treatment system. When the complete LFG to electricity process was analyzed, the internal combustion engine had the highest percentage of total capital investment and the total annual cost. For the base case, it became economically beneficial to install a SREU at facilities with LFG flowrates greater than ∼2000 m 3 /h. Sensitivity analysis showed that at a base case of 1700 m 3 /h, LFG (50% CH4 ), and 50 mg/m 3 D4, the net income of facilities in Scenarios 1 to 3 became positive at an electricity sales price greater than 5.5 cents/kWh. LCA revealed that Scenario 2 had the greatest CO2 emission reduction. Scenario 3 is observed to save less CO2 emissions as biogas flowrate increases due to frequent engine shutdowns. Although there are differences in the global warming potential (GWP 100) for Scenarios 1 to 3, with Scenario 2 being the best and Scenario 3 being the worst, the differences are very small. For this reason, economics alone are sufficient in decision making. Graphical abstract: Image 1 Highlights: TEA and LCA conducted on LFG to electricity with and without pretreatment. Siloxane removal unit economical in facilities with LFG flowrates over 2000 m 3 /h. Siloxane removal units with continuous operation results in lowest CO2 emissions. Source of avoided electricity on the global warming potential (GWP) was analyzed.